Fused Thiophene Semiconductors: Crystal Structure–Film Microstructure Transistor Performance Correlations. (13th March 2013) - Youn, Jangdae; Kewalramani, Sumit; Emery, Jonathan D.; Shi, Yanrong; Zhang, Shiming; Chang, Hsiu‐Chieh; Liang, You‐jhih; Yeh, Chia‐Ming; Feng, Chieh‐Yuan; Huang, Hui; Stern, Charlotte; Chen, Liang‐Hsiang; et al.
Abstract The molecular packing motifs within crystalline domains should be a key determinant of charge transport in thin‐film transistors (TFTs) based on small organic molecules. Despite this implied importance, detailed information about molecular organization in polycrystalline thin films is not available for the vast majority of molecular organic semiconductors. Considering the potential of fused thiophenes as environmentally stable, high‐performance semiconductors, it is therefore of interest to investigate their thin film microstructures in relation to the single crystal molecular packing and OTFT performance. Here, the molecular packing motifs of several new benzo[d, d′]thieno[3, 2‐b;4, 5‐b′]dithiophene (BTDT) derivatives are studied both in bulk 3D crystals and as thin films by single crystal diffraction and grazing incidence wide angle X‐ray scattering (GIWAXS), respectively. The results show that the BTDT derivative thin films can have significantly different molecular packing from their bulk crystals. For phenylbenzo[d, d′]thieno[3, 2‐b;4, 5‐b′]dithiophene (P‐BTDT), 2‐biphenylbenzo[d, d′]thieno‐[3, 2‐b;4, 5‐b′]dithiophene (Bp‐BTDT), 2‐naphthalenylbenzo[d, d′]thieno[3, 2‐b;4, 5‐b′]dithiophene (Np‐BTDT), and bisbenzo[d, d′]thieno[3, 2‐b;4, 5‐b′]dithiophene (BBTDT), two lattices co‐exist, and are significantly strained versus their single crystal forms. For P‐BTDT, the dominance of the more strained lattice relative to the bulk‐like lattice likely explains the high carrier mobility. In contrast, poor crystallinity and surface coverage at the dielectric/substrate interface explains the marginal OTFT performance of seemingly similar PF‐BTDT films.